Implementation of Technology and Housekeeping Innovations on Efficiency, Effectiveness and Employee Performance in The Galesong Tourist Area of Takalar Regency - Nasir, Muhammad Ersyad; Ab, Ahmad; Zulkifli, Andi Ade (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
This study analyses the impact of technology and innovation on operational performance in the housekeeping section of the tourist area in Takalar Regency. Data from employee interviews indicate that while technology adoption varies, advanced technology has increased efficiency, service quality, and customer satisfaction. Challenges include a lack of training and resistance to change. To overcome these, the study suggests investing in technology, employee training, and collaborating with technology providers. In conclusion, technology and innovation are crucial for enhancing productivity and customer satisfaction in the hospitality sector.